FriP cheese: the best cheese-making tradition for patients with impaired renal function - Maria Cristina Mancuso; Gianluigi Ardissino (Giornale di Clinica Nefrologia e Dialisi)
Patients with impaired renal function have several dietary limitations, including cheese for both its high phosphorus and sodium content. However, cheese is an important component of the European diet, and its limitation, together with the many other deprivations, negatively affects patients’ quality of life and nutrition. We have developed a cheese-making process characterized by the enrichment of milk with calcium carbonate to provide patients with a nutritional opportunity while improving their phosphorus control. The procedure can be applied to any type of milk and cheese. The derived products (identified by the designation of FriP) have optimal palatability, being indistinguishable from regular cheese. FriP cheese has a very low concentration of absorbable phosphorus and a low sodium content. FriP cheese has proven its efficacy in lowering phosphorus absorption in both healthy subjects and in chronic kidney disease (CKD) patients, as well as its safety as to calcium metabolism. Herein, we share the story of how FriP cheese has been developed to become an additional resource for overcoming some of the dietary limitations of patients with CKD towards better nutrition, phosphorus control, and quality of life.